A Subset of New Platinum Antitumor Agents Kills Cells by a Multimodal Mechanism of Action Also Involving Changes in the Organization of the Microtubule Cytoskeleton - Kostrhunova, Hana; Zajac, Juraj; Novohradsky, Vojtech; Kasparkova, Jana; Malina, Jaroslav; Aldrich-Wright, Janice R; Petruzzella, Emanuele; Sirota, Roman; Gibson, Dan; Brabec, Viktor (Journal of medicinal chemistry, 2019)
The substitution inert platinum agent [Pt(1 S,2 S-diaminocyclohexane)(5,6-dimethyl-1,10-phenanthroline)]2+ (56MeSS, 5) is a potent cytotoxic metallodrug. In contrast to conventional cisplatin or oxaliplatin, the mechanism of action (MoA) of 5 is fundamentally different. However, details of the mechanism by which the 5,6-dimethyl-1,10-phenanthroline ligand contributes to the cytotoxicity of 5 and its derivatives have not been sufficiently clarified so far. Here, we show that 5 and its Pt(IV) derivatives exhibit an intriguing potency in the triple-negative breast cancer cells MDA-MB-231. Moreover, we show that the Pt(IV) derivatives of 5 act by multimodal MoA resulting in the global biological effects, that is, they damage nuclear DNA, reduce the mitochondrial membrane potential, induce the epigenetic processes, and last but not least, the data provide evidence that changes in the organization of cytoskeleton networks are functionally important for 5 and its derivatives, in contrast to clinically used platinum cytostatics, to kill cancer cells.
Keywords: Animals; Cytoskeleton; DNA nádorová; křečci praví; Female; mikrotubuly; CHO buňky; Cell Line, Tumor; DNA, Neoplasm; ženské pohlaví; screeningové testy protinádorových léčiv; cytoskelet; nádorové buněčné linie; lidé; triple-negativní karcinom prsu; Antineoplastic Agents; protinádorové látky; Triple Negative Breast Neoplasms; Cricetulus; Ligands; organoplatinové sloučeniny; epigeneze genetická; Tubulin Modulators; aktiny; Actins; modulátory tubulinu; Epigenesis, Genetic; Drug Screening Assays, Antitumor; Microtubules; Organoplatinum Compounds; zvířata; ligandy; Cricetinae; CHO Cells; Humans